2018
DOI: 10.1186/s12891-018-2090-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcifediol (25-hydroxyvitamin D) improvement and calcium-phosphate metabolism of alendronate sodium/vitamin D3 combination in Chinese women with postmenopausal osteoporosis: a post hoc efficacy analysis and safety reappraisal

Abstract: BackgroundVitamin D (VD) insufficiency or deficiency is a frequent comorbidity in Chinese women with postmenopausal osteoporosis (PMO). The present study aimed to investigate 25-hydroxyvitamin D [25(OH) D] improvement and calcium-phosphate metabolism in Chinese PMO patients treated with 70 mg of alendronate sodium and 5600 IU of vitamin D3 (ALN/D5600).MethodsChinese PMO women (n = 219) were treated with 12-month ALN/D5600 (n = 111) or calcitriol (n = 108). Changes in 25(OH) D at month 12 were post hoc analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…[ 13 ] Moreover, the prevalence of hypovitaminosis D is more frequent in PM women compared to age-matched men. [ 14 ] These findings indicate that hypovitaminosis D is a common occurrence in PM women with CAD. Awareness and treatment for VitD deficiency are thus crucial interventions to improve CAD prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…[ 13 ] Moreover, the prevalence of hypovitaminosis D is more frequent in PM women compared to age-matched men. [ 14 ] These findings indicate that hypovitaminosis D is a common occurrence in PM women with CAD. Awareness and treatment for VitD deficiency are thus crucial interventions to improve CAD prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…A significant increase in the BMD of lumbar vertebrae, but not in the femoral neck and total hip, and serum 25(OH) vitamin D levels were identified with CaldD treatment alone for 9 months, compared with the baseline levels. A number of trials have reported on the beneficial effect of ALN in the treatment of bone deteriorations in post-menopausal women, as well as in GIOP and orthotopic liver transplantation-associated bone loss (13,16,17,20). A comparative study of ALN (10 mg/day), calcitriol or simple vitamin D supplementation in 195 glucocorticoid-treated subjects with a 2-year follow-up reported a significant increase in the mean lumbar vertebral BMD (+5.9%) with ALN treatment, compared with that achieved by calcitriol (-0.7%) or vitamin D (-0.5%) treatment (13).…”
Section: Discussionmentioning
confidence: 99%
“…During the 12 months, 219 women were treated with monthly alendronate/vitamin D3 ( n = 111) or calcitriol ( n = 108) 89P. The safety outcome measures included serum calcium and phosphate and 24 h urine calcium [73]. Absolute change in mean serum 25(OH) D level was the greatest in Vitamin D-deficient patients and least in Vitamin D-sufficient patients at months 6 and 12 (both p < 0.01).…”
Section: Clinical Opinionmentioning
confidence: 99%
“…Mean 24 h urine calcium slightly increased in the alendronate/vitamin D3 group and significantly increased in the calcitriol treatment group (+1.1 and +0.9 mmol/L at months 6 and 12; both p < 0.05). Calcitriol treatment was associated with more frequent hypercalciuria at month 6 (9.4% versus 18.5%, p = 0.05), but not at month 12 (12.3% versus 13.0%) [73]. They concluded that baseline Vitamin D status predicted 25(OH) D improvement in patients with 12 months of alendronate/vitamin D3 treatment.…”
Section: Clinical Opinionmentioning
confidence: 99%
See 1 more Smart Citation